Cushing’s Disease due to ACTH Secreting Pituitary Microadenoma: A Single Institutional Experience of Four Cases - Gandhi, Ashok; Barhate, Mayur V.; Jain, Shashikant K.; Gandhi, Sapna A. (Indian Journal of Neurosurgery, 2020)
ACTH secreting pituitary adenomas are rare occurrences in autoptical, surgical and neuroradiological series. We herewith describe a series of four patients of Cushing’s disease due to ACTH secreting pituitary microadenoma. All patients presented with signs and symptoms of hypercortisolism. Hormonal testing and bilateral inferior petrosal sinus sampling were indicative of pituitary-dependent Cushing’s syndrome. Dynamic sellar MRI was suggestive of asymmetric pituitary, with suspect pituitary microadenoma in all cases. Three patients were operated for endoscopic endonasal transsphenoidal surgery, while one patient refused surgery and was managed with ketoconazole. During postoperative period, remission of hypercortisolism was ensured in two patients, while one patient continued to have raised levels of cortisol. One patient with raised levels of cortisol during postoperative period was prescribed Ketoconazole for 6 months. Histopathology confirmed the presence of pituitary adenoma. Adenoma displayed ACTH immunoreactivity. Our cases indicate that ACTH secreting pituitary microadenoma may occur in patients with Cushing’s disease. Careful radiological, surgical and pathological examination is necessary to recognize this condition and avoid surgical failure.
Keywords: pituitary; ACTH; Cushing’s disease; microadenoma